Friendship Quality in Adolescents With ADHD. Issue 8 (June 2020) - Rokeach, Alan; Wiener, Judith
Objective: This study compared the quality of friendships (same- and other-sex) in adolescents with and without ADHD, across age and gender.Method: A community sample of 115 participants (61 ADHD, 54 Comparison), ages 13 to 18, completed a questionnaire assessing perceived levels of social support and negative interactions experienced in their friendships.Results: Ratings of friendship social support diminished across age in youth with ADHD, but increased in typically developing youth. Adolescents with and without ADHD, however, did not differ on ratings of negative interactions experienced in their friendships. Compared with males, females rated their friendships to be more supportive, irrespective of ADHD status. Adolescents with and without ADHD rated their same-sex friendships to be simultaneously more supportive and more conflictual than their other-sex friendships.Conclusion: Assessments of adolescents with ADHD should include a careful examination of their social functioning with particular attention devoted to the quality of their friendships.